74 Multisystem manifestations of cyanotic adult congenital heart disease: review of prevalence and current practice on the norpap database. (5th June 2017) - Abraham, Dilip; Baral, Ranu; Bingham, Ruth; Head, Catherine; Lewis, Clive; Freeman, Leisa J
Abstract : Introduction: Adults with congenital heart disease may be cyanotic either from unrepaired cyanotic conditions, or due to the failure of palliative procedures to completely separate the systemic and pulmonary circulations. Clinicians should be aware of the multisystem manifestations of chronic cyanosis. Chronic hypoxaemia leads to a physiological rise in haemoglobin and red cell mass, causing secondary erythrocytosis. Management includes avoidance of routine venesection, ensuring adequate hydration and avoiding iron deficiency. Complete iron studies should be carried out regularly since the MCV is a poor determinant of iron deficiency. Methodology: The NORPAP database was created in 1993 and contains 2854 patients from Norwich and Papworth. Patients with cyanotic heart conditions were extracted from the database and the prevalence of the following complications were sought from electronic letters: hyperviscosity symptoms, acne, gout, bleeding/haemoptysis, thromboembolism, brain abscess, stroke, endocarditis, renal dysfunction and gallstones (Table 1). In addition the management of erythrocytosis was assessed as satisfactory vs not satisfactory based on the following criteria annual FBC and complete iron studies including iron supplementation if indicated, and avoidance of routine venesection. Results: 102/2854 (3.5%) had cyanosis. PAH-CHD present in 70/102 (68.6%). F:M 1.76:1. Age range 21–81, mean 39, median 38. Death occurred in 26/102 (25.4%). Mean age at death 45, median 42. Cause of death Cardiac/PAH: 12/26, non-cardiac: 5/26, unknown: 9/26. In the Trisomy 21 group mean age at death 40, median 38. Underlying condition is shown in Figure 1. One patient with VSD Eisenmenger Syndrome had concomitant ischaemic heart disease, complicated by retroperitoneal bleeding secondary to dual antiplatelet therapy and low molecular weight heparin. Complete clinical information and blood results were available for 78/102 patients. Erythrocytosis: 66/78 (84.6%) satisfactory, 12/78 (15.3%) not satisfactory. This was predominantly on account of no iron studies. Conclusions: An understanding of the multisystem manifestations of cyanotic conditions and avoidance of common pitfalls is paramount in the management of these complex patients. We follow the ESC/AHA guidelines on antibiotic prophylaxis against endocarditis in high risk groups. None of the documented cases were related to dental procedures. Patients need careful assessment when considering anticoagulation given the balance of risk between bleeding and thromboembolism complications seen not infrequently in our population. Gout and renal dysfunction are common and should be actively sought during routine clinical assessment. On review of the data from this observational study, a clinic proforma to include a checklist of symptoms to screen for, in addition to FBC, Iron Studies, Uric Acid, and U and Es has been developed.